2000
DOI: 10.1177/0267323100015003007
|View full text |Cite
|
Sign up to set email alerts
|

From the Persian Gulf to Kosovo — War Journalism and Propaganda

Abstract: Sweden and the UK. A combined discourse and propaganda analysis approach is applied to the first three days' coverage of the NATO bombing campaign, with the aim of studying how the various national/local contexts influenced the media discourse's relationship to the propaganda discourse in the conflict. This problematic is relevant for the current discussion on globalization and superpower dominance in connection with transnational war journalism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
10

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 9 publications
0
19
0
10
Order By: Relevance
“…Grundmann, Smith, and Wright (2000) found thematic differences in French, British, and German establishment press coverage of the Kosovo crisis, despite these allies' similar interests. More specific to our questions about foreign policy statements, Norhstedt et al (2000) show systematic differences across Greek, Norwegian, Swedish, and British press coverage of U.S. President Bill Clinton's Kosovo crisis speeches. Gurevitch, Levy, and Roeh (1991) found diverging narrative and thematic structures in U.S. and British television coverage of a speech by then‐Soviet Communist Party Leader Mikhail Gorbachev.…”
Section: Motivated Reasoning and Media Discourse Narrowingmentioning
confidence: 90%
“…Grundmann, Smith, and Wright (2000) found thematic differences in French, British, and German establishment press coverage of the Kosovo crisis, despite these allies' similar interests. More specific to our questions about foreign policy statements, Norhstedt et al (2000) show systematic differences across Greek, Norwegian, Swedish, and British press coverage of U.S. President Bill Clinton's Kosovo crisis speeches. Gurevitch, Levy, and Roeh (1991) found diverging narrative and thematic structures in U.S. and British television coverage of a speech by then‐Soviet Communist Party Leader Mikhail Gorbachev.…”
Section: Motivated Reasoning and Media Discourse Narrowingmentioning
confidence: 90%
“…In both cases, journalists serve the public consensus and the common narratives; they do not present opposite views or alternative narratives, and they do not have an independent voice. A second way to identify a patriotic pattern of reporting is when the media follows the formal governmental or military framing of the event or conflict and does not provide the public with alternative frames of the story (see, for example, Katz, 1992; Nohrstedt et al, 2000; Ravi, 2005). Sometimes, when the majority of the public agrees with the government’s framing, or when the government purposely follows the common public view, the above two indicators – consensual narrative and governmental framing – merge into one.…”
Section: Patriotic Reporting: Explanations and Indicatorsmentioning
confidence: 99%
“…Using the democratic propaganda model, Nohrstedt et al (2000) examined media framing in the Kosovo conflict and found that the various national/local contexts are clearly visible in news coverage. During the era of the global war on terror, Snow and Taylor (2006: 390) also found that 'the enemy conducts propaganda as ''in ordinary practice'' whereas democracies ''tell the truth'', or at least as much of the truth as can be told to achieve victory while preserving those fundamental democratic values so cherished in normal times.'…”
Section: News As Propagandamentioning
confidence: 99%